2017
DOI: 10.1371/journal.pone.0179802
|View full text |Cite
|
Sign up to set email alerts
|

The impact of mobile phone use on where we look and how we walk when negotiating floor based obstacles

Abstract: Pedestrians regularly engage with their mobile phone whilst walking. The current study investigated how mobile phone use affects where people look (visual search behaviour) and how they negotiate a floor based hazard placed along the walking path. Whilst wearing a mobile eye tracker and motion analysis sensors, participants walked up to and negotiated a surface height change whilst writing a text, reading a text, talking on the phone, or without a phone. Differences in gait and visual search behaviour were fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 47 publications
3
33
0
1
Order By: Relevance
“…Furthermore, a recent study showed that the change in walking, during texting, may be attributed to the altered visual search behaviour [8]: the subjects may not be able to acquire sufficient visual information using the central visual field to plan direction of the walk with an increase of the risk of falling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a recent study showed that the change in walking, during texting, may be attributed to the altered visual search behaviour [8]: the subjects may not be able to acquire sufficient visual information using the central visual field to plan direction of the walk with an increase of the risk of falling.…”
Section: Discussionmentioning
confidence: 99%
“…Walking while using a mobile phone thus represents a dual-task and requires an appropriate division of attention [7]. It has been shown that the concurrent use of smartphone while performing other activities introduces cognitive distraction and drastically decreases field of vision and attention to the environment [8]. During walking it also reduces arm swing and alters head orientation, which may increase risk of falls [9].…”
Section: Introductionmentioning
confidence: 99%
“…The experiment started at 9:30 AM and continued till 11:30 AM. Participants were informed to keep walking as they normally would (similar to [16]). In order to observe pedestrian walking behavior at different flow states and different vending stall dimensions, 16 walking scenarios (matrix of 4 vendor types * 4 bidirectional flow rates) were conducted ( Table 1).…”
Section: Walking Scenariosmentioning
confidence: 99%
“…Pedestrian evasive action is a change in walking speed or lateral adjustment of walking path to maintain their personal space [13], [14]. However pedestrian evasive action could also be a result difference in pedestrian desired walking speed which for example lead to a move in lateral directions to overtake slow pedestrians [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…This ideal is generated from the observational study of building structure. Nowadays people always look on phone while walking and this trend affected how people look, research study proved this group of people were more caution toward things below their eye level (Timmis, et al,2017). Moreover, it is also hard to found message display on the lower corner of the building.…”
Section: Third Artwork: I Feel Miserable (2018)mentioning
confidence: 99%